The Effect of Pollination Models on Yield of Red Pitaya (Hylocereus polyrhizus) - Renfiyeni Renfiyeni (JERAMI : Indonesian Journal of Crop Science, 2018)
Red pitaya is getting more popular in Indonesia recently as one of high antioxidant sources with a promising economic value. However, the production of this CAM plant is restricted by low success percentage of its natural pollination and self incompatibility problems. Therefore, artificial pollination is required to overcome these problems and increase its yield. This study was aimed to evaluate the effect of pollination models towards the yield of red pitaya. This study was conducted using randomized block design with three pollination models applied into nine groups. Pollination models used were open pollination (P1), hand-self-pollination (P2) and hand-cross pollination (P3). Several floral-related parameters, including the elongation of flower bud, diameter of blooming flower, length of stigma, number and length of anthers, were assessed. Effect of different pollination models was also observed through some yield-related parameters, such as fruit weight, fruit diameter, fruit length, harvesting age and number of fruit sets. This study revealed that hand cross pollination produced the best yield performance showing 541.1 gram of fruit with 11.5 in length and 8.66 cm in diameter. Harvesting age and number of fruit sets showed no significant difference among those three pollination models. Keywords: Pollination, red pitaya, yields, fruits, flowers